2020
DOI: 10.3390/jpm10040290
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrospinal Fluid Penetration and Combination Therapy of Entrectinib for Disseminated ROS1/NTRK-Fusion Positive Pediatric High-Grade Glioma

Abstract: Targeting oncogenic fusion-genes in pediatric high-grade gliomas (pHGG) with entrectinib has emerged as a highly promising therapeutic approach. Despite ongoing clinical studies, to date, no reports on the treatment of cerebrospinal fluid (CSF) disseminated fusion-positive pHGG exist. Moreover, clinically important information of combination with other treatment modalities such as intrathecal therapy, radiotherapy and other targeted agents is missing. We report on our clinical experience of entrectinib therapy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 50 publications
1
24
0
Order By: Relevance
“…These analyses demonstrated the overall remarkable sensitivity of EPN towards various FGFRis with IC 50 s in the low-micromolar to nanomolar range. In general, the IC 50 values of FGFRis were comparable to FGFR-driven control models [ 14 ] but also to other RTK-driven pediatric brain cancer cell models including NTRK fusion-driven HGG cell models towards NTRK-inhibitors [ 9 , 39 ]. High sensitivity was observed not only for the multi-RTKi ponatinib, but also the more FGFR-specific AZD-4547 inhibitor, proving FGFRs as central therapeutic targets in EPN cells.…”
Section: Discussionmentioning
confidence: 88%
“…These analyses demonstrated the overall remarkable sensitivity of EPN towards various FGFRis with IC 50 s in the low-micromolar to nanomolar range. In general, the IC 50 values of FGFRis were comparable to FGFR-driven control models [ 14 ] but also to other RTK-driven pediatric brain cancer cell models including NTRK fusion-driven HGG cell models towards NTRK-inhibitors [ 9 , 39 ]. High sensitivity was observed not only for the multi-RTKi ponatinib, but also the more FGFR-specific AZD-4547 inhibitor, proving FGFRs as central therapeutic targets in EPN cells.…”
Section: Discussionmentioning
confidence: 88%
“…Mutations concerning either BRAF or NTRK fusions are of particular interest since they represent potentially targetable alterations. Data concerning inhibition has been encouraging in BRAF V600E mutant gliomas [ 89 ] as well as entrectinib in NTRK -fusion positive pHGG [ 90 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, Phase I studies for melanoma showed considerable side effects of this drug combination, which limited the drug exposure [ 66 , 68 ]. In our experience with combination of targeted treatment, also including everolimus and trametinib, the side effects were manageable for a certain period in pediatric patients, but combination therapy had to be discontinued eventually due to skin toxicity [ 69 ]. Nevertheless, we initiated this combination of treatment in the reported case, due to urgent clinical need.…”
Section: Discussionmentioning
confidence: 99%